PENGGUNAAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN NUMERASI SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Ari Lestari Handayani; Wiryanto; Andi Kristanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Numeracy skills are one of the basic competencies that are very important for students at the elementary school level, therefore the development of effective learning media is very important to improve students' numeracy skills. This study aims to analyze the development of learning media in improving elementary school students' numeracy skills through the Systematic Literature Review (SLR) approach. Numeracy skills are an important competency that students must have, but many still have difficulty in understanding basic mathematical concepts. In this study, 25 relevant articles were identified and analyzed, focusing on the effectiveness of various types of learning media, including digital, interactive, and conventional media.The results of the analysis show that digital learning media, such as mobile applications and e-learning platforms, significantly increase students' motivation and learning outcomes. The use of interactive media, such as smart boards and educational games, has also proven effective in improving students' understanding of numeracy concepts. In contrast, conventional media such as workbooks show lower effectiveness.This study emphasizes the importance of innovation in the development of learning media to meet students' learning needs in the digital era. Further efforts are needed to integrate technology and interactive approaches into the basic education curriculum in order to optimally improve students' numeracy skills.